Educação Ambiental em espaços não-formais: estudo de caso do projeto Aprendendo com a Mata Atlânica (Itu-SP) - Marchi, Kelly (Universidade Federal de São Carlos, 2023)
This project analyzes how non-formal environmental education has contributed to formal environmental education in schools. The object of study focuses on the project Learning wit the Atlantic Forest, with activities to milieu analysis, being developed by the SOS Mata Atlântica Foudation since 2010 at the Forestry Research Center SOS Mata Atlântica - HEIENKEN Group, located in Itu, São Paulo. The time frame of the research is limited to the year 2022, with 11 teachers from 6 schools as subjects. This is a case study and the methodological data collection procedures involve bibliographic and documentary review and fieldwork in an action research approach. The results obtained indicate the relevance of studying the environment in the educational training of students and teachers regarding environmental education and, therefore, the potential of non-formal educational spaces such as the Experiment Center in this context. It is concluded, with this work, that the Learning with the Atlantic Forest project has interfaces with the milieu analysis, is recognized by teachers about the educational potential and encourages developments for actions at school, in order to highlight and strengthen the positive relationship and proposal between formal and non-formal environmental education.
Environmental Education in non-formal spaces: case study of the Learning with the Atlantic Forest project (Itu - SP- BRAZIL)
Keywords: Educação ambiental; Estudo do meio; Mata Atlântica; Environmental education; Milieu analysis; Atlantic Forest; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM